Assessment of anti-trypanosomal drug resistance in cattle of the Ladduga Grazing Reserve, Kachia, Nigeria - Randolph, Thomas F.; Diall, O.; Clausen, Peter-Henning; Diarra, B.; Mamman, M.; Kalejaiye, J.O.; Shaida, S.S.; Fajinmi, A.O.; Samdi, S.K.; Wayo, B.; Okoh, E.; Ramatu, B.; et al. (2011)
A survey was conducted to determine the occurrence and magnitude of antitrypanosomal drug resistance in cattle of the Ladduga Grazing Reserve. The 310 cattle used in the study were randomly selected from each of the 6 blocks of the reserve. Blood samples obtained by venipuncture from the cattle were examined for trypanosomes by the Buffy Coat Technique and a PCR-based assay technique. Naturally occurring trypanosomal infections, diagnosed microscopically, in the cattle (No. detected parasitaemic/No. examined) were 11/71 (block I), 14/60 (block II), 39/54 (block III), 42/50 (block IV), 21/43 (block V) and 29/29 (block VI). In this study, we applied a protocol for rapid detection of anti-trypanosomal drug resistance hotspots which involved the monitoring of all the 156 cattle detected parasitaemic that were divided into two equal groups of 78 subjects each and treated on day 0 with diminazene aceturate (7.0 mg/kg, i.m.) or isometamidium chloride (0.5 mg/kg, i.m.). All treated cattle subsequently detected parasitaemic when re-examined on day 14 received treatment with the other “sanative pair” drug (i.e. diminazene in those previously treated with isometamidium, and vice versa). All the cattle treated on day 14 and subsequently detected parasitaemic on day 28 were treated with the other “sanative pair” drug. The infections included single infections with Trypanosoma brucei (8.9%), T. congolense (46.2%) and T. vivax (3.8%), and mixed infections of T. brucei /T. congolense (28.9%), T. congolense /T. vivax (7.1%), T. brucei /T. vivax (0.6%), and T. brucei /T. congolense /T. vivax (5.1%). Regardless of the Trypanosoma spp. found and nature (single/multiple) of the infection, the overall treatment failure rate determined on day 14 was 20.3% for isometamidium and 10.7% for diminazene. Data determined on day 28 indicated overall failure rates of 40.5% for treatment with isometamidium and 7.3% for that with the “sanative pair”. Based on response to questionnaire surveys, the herdsmen indicated that they readily purchased and self-administered diminazene or isometamidium to their cattle although only 20% of the respondents appeared to use the correct dosages of the two drugs. Data from the study would contribute to the mapping and control of animal trypanosomiasis in Nigeria and the West African cotton belt.